2003
DOI: 10.5902/198050981741
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da intensidade de desrama na produção de <i>Pinus elliottii</i> Engelm., no município de Piratini, RS.

Abstract: RESUMOEstudou-se a influência da intensidade de desrama sobre a produção de Pinus elliottii Engelm., no município de Piratini, RS, em um experimento em blocos ao acaso com quatro repetições e quatro tratamentos, definidos por: T1 -testemunha, sem desrama; T2 -desrama de 40% da altura total; T3 -desrama de 60% da altura total; T4 -desrama de 80% da altura total das árvores. Observou-se que o diâmetro e a produção de madeira foram fortemente influenciados pela intensidade da desrama, aos 13 anos de idade. Os res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
2
0
2
Order By: Relevance
“…As no previous studies related to pruning A. angustifolia could be found, some comparisons to the genus Pinus are given as follows. Hoppe and Freddo (2003) studied different pruning intensities in Pinus elliottii Engelm. in the state of Rio Grande do Sul, Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…As no previous studies related to pruning A. angustifolia could be found, some comparisons to the genus Pinus are given as follows. Hoppe and Freddo (2003) studied different pruning intensities in Pinus elliottii Engelm. in the state of Rio Grande do Sul, Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Vários trabalhos foram realizados sobre desrama artificial, os quais enfatizam, principalmente, o efeito da intensidade de desrama sobre o crescimento das árvores, a fim de se encontrar a melhor forma de aplicação da técnica. Geralmente os trabalhos sobre desrama consideram a quantidade de galhos e/ou folhas retirados do tronco de acordo com uma porcentagem em relação à altura total da árvore (SCHNEIDER et al, 1999;FINGER et al, 2001;PIRES et al, 2002;FREDDO, 2003), ou de acordo com a altura de desrama em relação ao nível do solo (PULROLNIK, 2002;ALMEIDA, 2003;POLLI, 2005;MONTE et al, 2009).…”
Section: Revisão Bibliográficaunclassified
“…As empresas que visam tal produção investem no manejo de suas florestas com a finalidade de aumentar a qualidade da madeira. Assim, a desrama artificial é uma técnica que tem a finalidade de diminuir a incidência de nós e com isso agregar valor à floresta, produzindo um material de alta qualidade, livre de defeitos e, principalmente, com maior resistência, durabilidade e beleza (SCHNEIDER et al, 1999;VALE, 2000;FINGER et al, 2001;PIRES et al, 2002;PULROLNIK, 2002;ALMEIDA, 2003;FREDDO, 2003).…”
Section: Introductionunclassified
“…According to Cezana et al (2012), timber companies have sought logs of high quality and yield, which is achieved through investment in adequate management. Artificial pruning is one of the practices that assists in the production of high-quality, defect-free timber, by increasing its strength, durability, and beauty in eucalyptus plantations (Vale et al, 2002;Finger et al, 2001;Pires et al, 2002;Hoppe and Freddo, 2003;Polli et al, 2006). The efficiency of artificial pruning is dependent on the age of the plants, the clonal material, as well as area to area, some authors have reported artificial pruning from 20 to 70%, depending on the size of the plants and spacing between plants used (Ferraz Filho et al, 2016a;Ferraz Filho et al, 2016b;Cezana et al, 2012).…”
Section: Introductionmentioning
confidence: 99%